2007
DOI: 10.3748/wjg.v13.i16.2289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbal medicine Juzentaihoto on hepatic and intestinal heat shock gene expression requires intestinal microflora in mouse

Abstract: Intestinal microflora affects multi-herbal product JTX on the gene expression in the gut and liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…42 Lactobacillus johnsonii may be involved in increased intestinal iHSP70 response to Juzentaihoto in mice. 70 Further links between the gut commensal microbiota and iHSPs in vivo were recently demonstrated in growing pigs. 65 Ileal HSP27 was found to correlate negatively with particular luminal bacteria (Lactobacillus reuteri and Enterobacteriaceae) ( Table 4).…”
Section: Inducible Heat-shock Proteins and The Gut Microbiota Gut Micmentioning
confidence: 95%
See 1 more Smart Citation
“…42 Lactobacillus johnsonii may be involved in increased intestinal iHSP70 response to Juzentaihoto in mice. 70 Further links between the gut commensal microbiota and iHSPs in vivo were recently demonstrated in growing pigs. 65 Ileal HSP27 was found to correlate negatively with particular luminal bacteria (Lactobacillus reuteri and Enterobacteriaceae) ( Table 4).…”
Section: Inducible Heat-shock Proteins and The Gut Microbiota Gut Micmentioning
confidence: 95%
“…58 Finally, the herbal medicine Juzentaihoto (Shi-Quan-Da-Bu-Tang in Chinese) was clearly shown to require the gut microbiota for stimulating intestinal HSP70 mRNA expression in mice, as no response occurred in germ-free animals. 70 Many gram-positive bacteria present in the human gut microbiota, such as Bifidobacterium breve, Lactobacillus paracasei, and Lactobacillus plantarum (but not Enterococcus faecalis), could induce expression of iHSP27 in Caco2 brush-border-expressing (Caco2-bbe) cells (Table 3). 30,39,40,43,44,71,72 A synthetic pentapeptide, also known as competent and sporulating factor from Bacillus subtilis, was shown to induce expression of HSP27 and protect gut epithelial cell (GEC) lines from oxidant injury.…”
Section: Inducible Heat-shock Proteins and The Gut Microbiota Gut Micmentioning
confidence: 99%
“…Given the comprehensive involvement and significant contribution of gut microflora to host physiology, we conceive that the gut microflora may be a major targeting site for TCM intervention, which exerts its holistic effects through multiple components to normalize disturbed physiological states. A series of pilot studies have recently revealed an interactive relationship between gut microflora and traditional medicines, involving two important aspects: gut microflora-dependent drug metabolism and gut microflora-targeted modulation of physiological conditions by traditional medicines (Kato et al, 2007;Sun et al, 2001;Yadav et al, 2007). These studies highlight the significance of gut microflora involvement in future investigation in the field of traditional medicines.…”
mentioning
confidence: 99%
“…They found the heat shock protein (HSP) gene expression changed only in the conventional mice but not in the germ-free mice, and the TCM decreased unculturable bacteria and increased Lactobacillus johnsoni, indicating the changes in the gut microbiota are necessary for the TCM formula to exert its modulation effects on HSP gene expression. 41 The transformation of predrug components of TCMs by the gut microbiota into active and bioavailable compounds is critical for the therapeutical effects of TCMs. Puerarin and daidzin are the main isoflavones in the rhizome of Pueraria thunbergiana that is one common TCM, but their estrogenic effects are weak.…”
Section: (Ii) the Integral Role Of The Gut Microbiome In Chronic Dismentioning
confidence: 99%